Molecular dynamics simulation of collagen binding to an amyloid-beta monomer and its effect on the peptide structure - Zakaria, Norzalina; Faujan, Nur Hana; Mohammad Latif, Muhammad Alif; Azaman, Siti Nor Ani; Mat Azmi, Intan Diana; Hassan, Nadiatul Hafiza; Azhar, Muhammad Fitri (Malaysian Institute of Chemistry, 2021)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease associated with the accumulation of amyloid beta (Aβ) peptides in the central nervous system (CNS). The extracellular matrix (ECM) proteins play an important role in the AD process. Fibrillar type III collagen is one of the major constituents of the ECM, providing the tissue with tensile strength and influencing cell attachment and migration. However, its structural properties and the binding mechanism of the Aβ42 monomer with type III collagen at the molecular level are largely unknown. In this study, the binding interactions of type III collagen with the Aβ42 monomer and the conformational dynamics of the Aβ42 monomer were investigated through molecular docking and molecular dynamics (MD) simulations. Docking results showed that type III collagen formed hydrogen bonds and hydrophobic contacts with the N-terminal, hydrophobic (CHC and SHR) and C-terminal regions of the Aβ42 monomer. Whereas MD results revealed that type III collagen reduced the helical content and promoted an aggregation-prone β-sheet conformation in the Aβ42 peptide structure. This finding suggests that type III collagen, and possibly other collagens, may play a role in regulating amyloid fibril formation. The results indicate that the localization of type III collagen may be an important initial event in amyloid plaque formation. Thus, our findings provide a preliminary understanding of the interaction of the Aβ peptide with type III collagen in Alzheimer’s disease.